Geographic Variation in Access to Plastic Surgeons. Issue 2 (February 2016) - Bauder, Andrew R.; Sarik, Jonathan R.; Butler, Paris D.; Noone, R. Barrett; Fischer, John P.; Serletti, Joseph M.; Kanchwala, Suhail K.; Kovach, Stephen J.; Fox, Justin P.
Abstract : Introduction: While recent studies project a national shortage of plastic surgeons, there may currently exist areas within the United States with few plastic surgeons. We conducted this study to describe the current geographic distribution of the plastic surgery workforce across the United States. Methods: Using the 2013 to 2014 Area Health Resource File, we estimated the number of plastic surgeons at the health service area (HSA) level in 2010 and 2012. The density of plastic surgeons was calculated as a ratio per 100, 000 population. The HSAs were grouped by plastic surgeon density, and population characteristics were compared across subgroups. Characteristics of HSAs with increases and decreases in plastic surgeon density were also compared. Results: The final sample included 949 HSAs with a total population of 313, 989, 954 people. As of 2012, there were an estimated 7600 plastic surgeons, resulting in a national ratio of 2.42 plastic surgeons/100, 000 population. However, over 25 million people lived in 468 HSAs (49.3%) without a plastic surgeon, whereas 106 million people lived in 82 HSAs (8.6%) with 3.0 or more/100, 000 population. Plastic surgeons were more likely to be distributed in HSAs where a higher percentage of the population was younger than 65 years, female, and residing in urban areas. Between 2010 and 2012, 11 HSAs without a plastic surgeon increased density, whereas 15 HSAs lost all plastic surgeons. Conclusions: Plastic surgeons are asymmetrically distributed across the United States leaving over 25 million people without geographic access to the specialty. This distribution tends to adversely impact older and rural populations.